2002
DOI: 10.1093/rheumatology/41.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and changes in the activity of systemic lupus erythematosus

Abstract: Depression and anxiety scores parallel changes in patients' assessments of the activity of their SLE. We found no evidence to support the hypothesis that psychological distress causes increased SLE activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
3
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 15 publications
5
51
3
4
Order By: Relevance
“…17 Other studies show similarity to the results of this research with respect to mean age at the time of diagnosis. 2,16,[18][19][20]24 The diagnosis of SLE is always a nuisance, 21 leaving young women anxious because it occurs in a productive and crucial phase of their life, a time to stabilize their relationships, constitute a family, or choose a career. The author's argument quoted previously is consistent with the results of this study, as the SLE patients were on average 34 years old, but at the time of SLE diagnosis they were on average six years younger.…”
Section: Discussionmentioning
confidence: 99%
“…17 Other studies show similarity to the results of this research with respect to mean age at the time of diagnosis. 2,16,[18][19][20]24 The diagnosis of SLE is always a nuisance, 21 leaving young women anxious because it occurs in a productive and crucial phase of their life, a time to stabilize their relationships, constitute a family, or choose a career. The author's argument quoted previously is consistent with the results of this study, as the SLE patients were on average 34 years old, but at the time of SLE diagnosis they were on average six years younger.…”
Section: Discussionmentioning
confidence: 99%
“…Estes dados vão de encontro a diversos estudos que evidenciam que a morbilidade psicológica está correlacionada positivamente com a actividade da doença (Bachen, 2006;Bae et al, 2001;Ishikura et al, 2001;Lim & Boey, 1991;Ward, Marx & Barry, 2002;Yoko et al, 2002).…”
Section: Quadro 1 Estrutura Factorial Do Fadigue Severity Scale (Fss)unclassified
“…Tench et al (2000) have suggested that myalgia and arthralgia related to lupus may disturb sleep, resulting in daytime fatigue. Increased levels of anxiety and depression are also associated with increased SLErelated fatigue (Ward 2002).…”
Section: Case Study: Fibromyalgia In Slementioning
confidence: 99%